Relationship Between Social Support and Work-Family Conflict: A Case Study of Women Employees in a Malaysian Higher Education Institution - Noor, Tahmina; Mohamad, Marlina; Dahri, & Salma (Journal of Technical Education and Training, 2019)
Work-family conflict (WFC) is a relatively less studied construct in the Eastern world and even sparser in the academic literature regarding working women in Malaysia. This paper is one of the few studies to examine social support mechanism used to alleviate such conflicts. The study examined the relationship between social support from work domain (supervisor support) and family domain (family support) addressing both directions of the conflict, work-to-family (W-to-FC) and family-to-work conflict (F-to-WC). A total of 278 women employees (146 academics and 132 non-academics) at a Malaysian Technical University participated in the study. The well-established instrument in work family literature was used to collect data via a survey. The results indicated a moderate level but relatively high mean value of W-to-FC than F-to-WC reported by women. Contradictory to a large body of work-family literature, the Pearson correlation analysis showed that work-family specific supervisor support is not related to either directions of work-family conflict (WFC) for Malaysian women. Social support provided by family however, was found to be statistically and negatively related to both directions of conflict. Findings from this study contribute to the understanding of the role of informal workplace social support by supervisor and family support with WFC in Malaysian educational institutions specifically in TVET. The results showed that women employees do experience WFC and supervisor work-family support is not enough to mitigate these conflicts. Hence, to produce women role models and retain them in the workplace, TVET higher learning institutions such as universities need to look into other workplace social support (like, family friendly policies, maternal leave, onsite childcare) to reduce the conflict for women employees.